2013
DOI: 10.1038/nature12578
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a Na+-bound Na+,K+-ATPase preceding the E1P state

Abstract: Na(+),K(+)-ATPase pumps three Na(+) ions out of cells in exchange for two K(+) taken up from the extracellular medium per ATP molecule hydrolysed, thereby establishing Na(+) and K(+) gradients across the membrane in all animal cells. These ion gradients are used in many fundamental processes, notably excitation of nerve cells. Here we describe 2.8 Å-resolution crystal structures of this ATPase from pig kidney with bound Na(+), ADP and aluminium fluoride, a stable phosphate analogue, with and without oligomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
387
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 284 publications
(425 citation statements)
references
References 51 publications
24
387
1
13
Order By: Relevance
“…The sequence of cytoplasmic Na + binding at the three sites of the Na + ,K + -ATPase is unsettled (4,26). The present data are consistent with the crystal structure-based proposal that the Na + ion at site III is the first ion to bind, followed by occupation of sites I and II, respectively, in a sequential and cooperative binding mechanism (4).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The sequence of cytoplasmic Na + binding at the three sites of the Na + ,K + -ATPase is unsettled (4,26). The present data are consistent with the crystal structure-based proposal that the Na + ion at site III is the first ion to bind, followed by occupation of sites I and II, respectively, in a sequential and cooperative binding mechanism (4).…”
Section: Discussionsupporting
confidence: 79%
“…The relatively minor reduction of the apparent affinity of sites I/II for Na + in C932R could be due to interference with the cooperative interaction between these sites and site III and/or to the tethered cation forcing an order of binding of cytoplasmic Na + different from the normally preferred order. In any case, our data are fully consistent with phosphorylation being controlled by binding of the last Na + to a site different from site III, in agreement with the evolutionary attractive hypothesis proposing that site II, the only transport site conserved in all P-type ATPases, is the last to be occupied from the cytoplasm, triggering the phosphorylation reaction in all P-type ATPases (4,14).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding that cholesterol both stabilizes in the presence of SOPS and enhances inhibition by SM or 18:0/18:0 PC suggests that there are more than one binding site. A recent high resolution structure of Na,K-ATPase revealed that cholesterol is bound to at least two sites (17). One cholesterol was observed in the ␣M8 -10 pocket next to the FXYD protein, a location we recently reported to be interacting with SOPS (29) (see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High resolution structures of SERCA, which were obtained for several conformations, revealed that the conformational transitions require substantial movements of TM1-6 3 as well as rearrangements of the three cytoplasmic domains (11). Until now, Na,K-ATPase has been crystallized in only three conformations either from shark rectal gland or pig kidney: E 2 ⅐MgF 4 2Ϫ ⅐2K ϩ (12,13) and E 2 ⅐MgF 4 2Ϫ ⅐2K ϩ ⅐ouabain (14), E 2 P⅐ouabain (15,16), and E 1 ⅐AlF 4 Ϫ ⅐ADP⅐3Na ϩ (17,18).…”
mentioning
confidence: 99%